TOPICAL ISSUES OF INCREASING INFORMATION ON THE VACCINE AGAINST HUMAN PAPILLOMA VIRUS IN UZBEKISTAN - Iskandarova, G.T.; Rakhmanova, J.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: To study the awareness of the population and medical workers about vaccination and the HPV vaccine in Uzbekistan. Material and methods: By anonymous questioning among the population, a survey of 386 people aged 18-72 years was conducted, both men and women selected by random sampling. In addition, 155 medical workers who came to study at the Tashkent Institute for Advanced Training of Doctors for Advanced Training, the following specialties: epidemiologists, a nurse with higher education, HLS methodologists, obstetrician-gynecologists, pediatricians, and GPs were also anonymously interviewed. The questionnaire consists of 20 questions. Results: The need for the dissemination of high-quality and highly evidence-based information on immunization, in addition to specialists, is also required by the population. Medical workers are well aware of the need for vaccination, 96.1% of respondents themselves when they receive information from medical professionals decide on immunization. But at the same time, there are problems in the awareness of medical workers about the new HPV vaccine, the effectiveness of vaccination, side effects, and safety. Conclusions: Medical workers are the main source of information for the population, therefore, public awareness depends on the knowledge and availability of information by the medical worker.